GREEN FINTECH AND ITS INFLUENCE ON SUSTAINABLE FINANCIAL PRACTICES - Rahul Autade (IJRDO - Journal of Business Management, 2023)
The increasing urgency of climate change and global sustainability concerns has positioned Green Fin Tech as a transformative force in sustainable banking. By leveraging digital innovations, Green Fin Tech minimizes the environmental footprint of financial services while enhancing operational efficiency. This paper explores the role of Green Fin Tech in sustainable banking, emphasizing the impact of artificial intelligence (AI), block chain, big data analytics, and cloud computing on the financial ecosystem. These technologies facilitate eco-friendly investments, regulatory compliance, and transparency in sustainable finance. The digitalization of financial services through Green Fin Tech significantly reduces paper consumption and energy use. Energy-efficient mobile banking applications, digital payment systems, and AI-driven risk assessment models optimize resources while allocating funds for green financing. Additionally, block chain technology enhances auditability and traceability in trading green bonds and carbon credits, ensuring credibility in sustainable investments. Big Data analytics further strengthens sustainable banking by enabling financial institutions to assess climate-related risks, refine green credit scoring, and develop climate-smart investment strategies. These advancements underscore the importance of collaboration among policymakers, financial institutions, and FinTech developers to accelerate the adoption of Green FinTech solutions. By integrating sustainability as a core pillar of financial innovation, the financial sector can drive long-term environmental and economic resilience.